Learning to Embody the Radically Empirical: Performance, Ethnography, Sensorial Knowledge and the Art of Tabla Playing - Nuttall, Denise (Anthropologica, 2018)
Cultural anthropology has privileged the concept of experience over that of performance, and as ethnographers, we have also privileged the ethnographic text and inscription over the act(s) of fieldwork or the “performances” of ethnography. Although we have made some improvements toward a different kind of anthropology, one that is embodied, the investigations of the body and performance have ultimately remained on the margins of the discipline. Drawing from my ethnographic participant fieldwork with North Indian tabla players and the teaching of ethnomusicology labs at an American university, I argue for a turn to what Sarah Pink (2009) has called sensory ethnography.